An abdominal asimmetry in a 17 years old girl - M.G. Scarpa; S. Norbedo; F. Murru; M. Bortul; R. Bussani; J. Schleef (PAGEPress Publications, 2012)
The pseudopapillary pancreatic solid tumor (TPSP) is a rare malignancy typical of young adult women (only 12 pediatric cases from 2000 to 2009), it can recur and metastasize. The prognosis is usually good after radical surgical removal. We emphasize the importance of TPSP in differential diagnosis of retrogastric, peripancreatic masses especially in puberal females. We describe the case of an adolescent girl with an abdominal mass revealed as a rare pancreatic neoplasia.